Battery cell and method for producing the same, battery, electric device

CN122950554APending Publication Date: 2026-10-20CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510457778.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2026-10-20

Smart Images

  • Figure BDA0005356195170000161
    Figure BDA0005356195170000161
  • Figure BDA0005356195170000171
    Figure BDA0005356195170000171
  • Figure BDA0005356195170000191
    Figure BDA0005356195170000191
Patent Text Reader

Abstract

A battery cell, its preparation method, the battery, and an electrical device are disclosed. The battery cell includes a negative electrode sheet, which includes a negative electrode active material layer. The negative electrode active material layer includes a negative electrode active material and a lithium-supplementing material. The lithium-supplementing material includes a coating layer and lithium material, with the coating layer covering at least a portion of the surface of the lithium material. The coating layer includes modified polyurethane, which has an aromatic structure. The technical solution of this application can improve the first-cycle coulombic efficiency and cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and more specifically, to a battery cell and its preparation method, a battery, and an electrical device. Background Technology

[0002] In recent years, with the increasingly wide range of applications, batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric cars, military equipment, aerospace, and many other fields. While batteries have achieved tremendous development, higher requirements have also been placed on their performance in various aspects.

[0003] During the first charge and discharge cycle of a battery, the electrolyte reacts with the negative electrode active material layer at the solid-liquid interface to form a stable solid electrolyte interface (SEI). However, the formation of the SEI layer can affect battery performance. For example, in lithium-ion batteries, the formation of the SEI layer consumes some lithium ions, thus affecting the battery's initial coulombic efficiency and cycle performance.

[0004] Therefore, improving the first-cycle coulombic efficiency and cycle performance of batteries is an urgent problem to be solved. Summary of the Invention

[0005] This application is made in view of the above-mentioned issues, and its purpose is to provide a battery cell and its preparation method, battery, and power device that can improve the first-cycle coulombic efficiency and cycle performance of the battery.

[0006] In a first aspect, a battery cell is provided, comprising: a negative electrode sheet, the negative electrode sheet including a negative electrode active material layer, the negative electrode active material layer including a negative electrode active material and a lithium replenishing material; the lithium replenishing material including a coating layer and a lithium material, the coating layer coating at least a portion of the surface of the lithium material; the coating layer including modified polyurethane, the modified polyurethane including an aromatic structure.

[0007] Coating the surface of lithium materials with modified polyurethane enhances the stability of the negative electrode. This modified polyurethane contains aromatic structures, which introduce hierarchical functional groups to achieve low-polarity hydrophobicity, repelling water and oxygen molecules and giving the modified polyurethane strong hydrophobicity. This provides good protection for the lithium material before electrolyte injection during battery cell fabrication. Simultaneously, the ester groups help improve wettability and affinity with the electrolyte, allowing the coating layer to dissolve in the electrolyte after injection, releasing lithium material for lithium replenishment. This design enables effective lithium replenishment of the negative electrode, thereby improving the battery's first-cycle coulombic efficiency and cycle performance.

[0008] In some embodiments, the modified polyurethane includes at least one selected from polyurethane-polyimide copolymer, polyurethane-polycarbonate copolymer, and polyurethane-polystyrene copolymer.

[0009] Using the above-mentioned modified polyurethane is beneficial to further enhance the stability of the coating layer 1211.

[0010] In some embodiments, the molecular weight (MW) of the modified polyurethane satisfies: 100000≤MW≤1000000.

[0011] Setting the molecular weight of the modified polyurethane within this range ensures that the waterproofness, mechanical hardness, and thermal stability of the coating layer are not affected by too low a molecular weight, nor is the flexibility and affinity for the electrolyte reduced by too high a molecular weight.

[0012] In some embodiments, the thickness H of the coating layer satisfies: 10μm≤H≤100μm.

[0013] Setting the thickness of the coating layer 1211 within the above range is beneficial to reduce the impact of excessively thin thickness on the coating effect, and also beneficial to reduce the impact of excessively thick thickness on the release rate of lithium material, as well as the kinetic performance and energy density of the battery.

[0014] In some embodiments, the mass ratio ω1 of the lithium replenishment material to the negative electrode active material layer satisfies: 0.5% ≤ ω1 ≤ 10%.

[0015] If ω1 meets the above range, the lithium replenishment effect will not be affected by insufficient lithium replenishment material, nor will the structure of the electrode be damaged by excessive lithium replenishment material.

[0016] In some embodiments, the mass ratio ω2 of the lithium material to the negative electrode active material layer satisfies: 0.1% ≤ ω2 ≤ 5%.

[0017] Maintaining a lithium material to negative electrode active material layer mass ratio within the aforementioned range can reduce both the reduced lithium replenishment effect due to insufficient lithium material and the residual lithium material problem caused by excessive lithium material. Specifically, residual lithium material may cause internal short circuits in the battery or lithium plating on the negative electrode, thereby affecting the overall performance of the battery.

[0018] In some embodiments, the lithium material includes metallic lithium and lithium-containing compounds.

[0019] Based on the actual usage requirements of the battery cells, appropriate lithium materials can be selected.

[0020] In some embodiments, the lithium metal includes at least one of lithium powder and lithium foil.

[0021] Lithium powder has a high specific surface area and high reactivity, requiring operation in an inert environment. It is suitable for applications requiring efficient lithium replenishment and uniform distribution. Lithium foil, on the other hand, is relatively stable and easy to handle, making it suitable for applications that are simple to operate but do not have high requirements for lithium replenishment efficiency and uniformity.

[0022] In some embodiments, the particle size D of the lithium powder satisfies: 1μm≤D≤100μm.

[0023] Setting D within the aforementioned range helps to reduce the risk of lithium powder agglomeration due to excessively small particle size, which reduces reactivity and impacts lithium replenishment efficiency. Conversely, it also helps to reduce the risk of lithium powder being too large, which reduces specific surface area, resulting in lower reactivity and uneven lithium replenishment, thus lowering lithium replenishment efficiency and processing performance.

[0024] In a second aspect, a battery is provided, comprising a battery cell as described in the first aspect and any possible implementation thereof.

[0025] Thirdly, an electrical device is provided, including the battery described in the second aspect. Attached Figure Description

[0026] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0027] Figure 1 This is a schematic diagram of the material of a lithium replenishment material according to an embodiment of this application;

[0028] Figure 2 This is a schematic diagram of a battery cell according to one embodiment of this application;

[0029] Figure 3 This is a schematic diagram of the structure of a battery cell according to another embodiment of this application;

[0030] Figure 4 This is a flowchart illustrating the preparation process of a battery cell according to one embodiment of this application.

[0031] Figure 5 This is a flowchart illustrating the preparation process of the negative electrode sheet according to one embodiment of this application;

[0032] Figure 6 This is a flowchart illustrating the preparation of the negative electrode sheet according to another embodiment of this application.

[0033] Figure 7 This is a schematic diagram of a battery according to one embodiment of this application;

[0034] Figure 8 This is a schematic diagram of the structure of a battery according to one embodiment of this application;

[0035] Figure 9 This is a schematic diagram of the structure of an electrical device according to an embodiment of this application;

[0036] Figure 10 This is a SEM image of a lithium replenishment material according to an embodiment of this application;

[0037] Figure 11 This is a Fourier transform infrared spectrum of a modified polyurethane according to an embodiment of this application.

[0038] Figure label:

[0039] 1-Vehicle; 11-Shell; 12-Electrode assembly; 121-Lithium replenishment material; 1211-Covering layer; 1212-Lithium material; 13-Cover plate; 100-Battery cell; 400-Battery assembly; 401-Upper housing; 402-Lower housing; 500-Motor; 600-Controller.

[0040] The accompanying drawings are not drawn to scale. Detailed Implementation

[0041] The following detailed description of the battery cell, its preparation method, battery, and power-consuming device of this application, with appropriate reference to the accompanying drawings, may omit unnecessary details. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0042] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0043] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0044] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0045] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0046] Battery performance is closely linked to its interface stability, including the interface between the electrode plates and the electrolyte. During the first charge and discharge cycle, the electrolyte and the negative electrode active material react at the solid-liquid interface to form a stable solid electrolyte interface (SEI) film. For example, in lithium-ion batteries, this process inevitably consumes some lithium ions, and this consumption is irreversible. If the consumption of lithium ions exceeds a reasonable range, the overall performance of the battery will be significantly affected. Therefore, reducing irreversible lithium ion loss is crucial for improving the battery's initial coulombic efficiency and long-term cycle stability.

[0047] To address the aforementioned issues, one approach is to modify the SEI layer growth through structural modification. For example, nanostructure design or interface engineering of electrode materials can reduce lithiation side reactions, thereby improving battery performance. However, this method currently cannot completely eliminate lithium-ion loss. Another approach is to add additional lithium storage to the cathode material. For instance, over-lithiation can be performed by adding an extra lithium source to the cathode material to compensate for irreversible lithium loss during the first charge-discharge cycle. However, this method has limited lithium-ion storage capacity and easily damages the cathode material's structure. Furthermore, related technologies also improve battery performance through pre-lithiation of the anode; however, this method is currently limited to preparing the anode sheet in a non-aqueous environment. This not only restricts the anode preparation process but also complicates the process and imposes high environmental requirements on the preceding steps. Therefore, how to reduce the consumption of active lithium ions more directly, thereby improving the battery's first-cycle coulombic efficiency and cycle performance, is a pressing issue that needs to be addressed.

[0048] In view of the above, this application provides a battery cell and its preparation method, battery, and power device. The battery cell includes: a negative electrode sheet, the negative electrode sheet including a negative active material layer, the negative active material layer including a negative active material and a lithium supplement material; the lithium supplement material includes a coating layer and a lithium material, the coating layer covering at least a portion of the surface of the lithium material; the coating layer includes modified polyurethane, the modified polyurethane including an aromatic structure.

[0049] In the above technical solution, the coating layer on the surface of the lithium material is a modified polyurethane, which includes an aromatic structure. This structure can introduce hierarchical functional groups from functional group molecules to achieve low-polarity hydrophobic functional groups, which can repel water and oxygen molecules, giving the modified polyurethane strong hydrophobicity. This provides good protection for the lithium material before electrolyte injection during the preparation of the battery cell, improving the stability of the negative electrode. Simultaneously, its ester groups facilitate the solubility and affinity for the electrolyte, allowing the coating layer to dissolve in the electrolyte after injection, thereby releasing the lithium material and achieving lithium replenishment. Therefore, using the above-mentioned negative electrode facilitates more direct lithium replenishment to the negative electrode, thereby improving the battery's first-cycle coulombic efficiency and cycle performance.

[0050] [Battery cell]

[0051] This application provides a single battery cell. Typically, a single battery cell includes a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions repeatedly insert and extract between the positive and negative electrodes. The electrolyte acts as a conductor between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily reduces short circuits between the positive and negative electrodes while allowing ions to pass through.

[0052] Next, the negative electrode, positive electrode, electrolyte, and separator of this application will be described with appropriate reference to the accompanying drawings.

[0053] [Negative electrode plate]

[0054] The negative electrode sheet may include a negative current collector and a negative active material layer disposed on at least one surface of the negative current collector, wherein the negative active material layer includes a negative active material and a lithium supplementation material.

[0055] Figure 1 This is a schematic diagram of the material of the lithium replenishment material 121 according to an embodiment of this application. Figure 1 As shown, the lithium replenishment material 121 includes a coating layer 1211 and a lithium material 1212, wherein the coating layer 1211 covers at least a portion of the surface of the lithium material 1212.

[0056] It should be noted that the coating here can be a complete coating of the lithium material 1212 or a partial coating of the lithium material 1212.

[0057] In this embodiment, the coating layer 1211 helps improve the stability of the negative electrode sheet. Specifically, lithium material 1212 is prone to reacting with moisture and oxygen in the air in a dry environment, causing surface deterioration and the formation of unstable compounds. This not only affects battery performance but may also increase the probability of battery thermal runaway. By providing a coating layer 1211 on the surface of lithium material 1212, direct contact between it and the external environment can be effectively isolated, reducing the occurrence of side reactions. Therefore, the coating layer 1211 helps enhance the chemical and mechanical stability of the negative electrode sheet.

[0058] In some embodiments, the coating layer 1211 comprises a modified polyurethane having an aromatic structure.

[0059] Polyurethane's molecular structure contains ester groups, giving it good solubility in electrolytes. This solubility is beneficial for the release process of lithium 1212. However, polyurethane molecules typically contain hydrophilic groups, such as ether bonds, which make them prone to forming hydrogen bonds with water molecules, resulting in poor water barrier properties. Simultaneously, the presence of urethane groups in the polyurethane molecular structure makes it easily modifiable. By polymer modification, adjusting the ratio of flexible to rigid segments in the copolymer molecular chain, or introducing functional groups, its physicochemical properties can be controlled to meet different application requirements.

[0060] Based on this, the modified polyurethane in this application introduces an additional hydrophobic structure, namely an aromatic structure, into the polyurethane. On the one hand, this structure introduces a layered approach from the functional group molecule level, achieving low-polarity hydrophobic functional groups that repel water and oxygen molecules. This results in the coating layer 1211 having a repulsive effect on water molecules, giving it better overall water-repellent properties. This water-repellent property is beneficial for protecting the lithium material 1212 before the electrolyte is injected into the negative electrode, thereby achieving a better lithium replenishment effect. On the other hand, the modified polyurethane can maintain the polyurethane's own solubility in the electrolyte. Its carbonyl functional groups can interact with the polar solvent in the electrolyte, weakening the intermolecular forces, improving the flexibility of the molecular chain and chemical compatibility, thereby enhancing the solubility in the electrolyte. Therefore, this modified polyurethane possesses both water-repellent and electrolyte-sustaining properties, which is beneficial for achieving spontaneous inert / active switching of the lithium material 1212 before and after electrolyte injection, thereby achieving negative electrode lithium replenishment and improving battery performance.

[0061] In practical applications of batteries, the water-repellent properties of the aforementioned coating layer 1211 are beneficial to the actual battery manufacturing process. Specifically, the coating layer 1211 not only effectively reduces the contact between the lithium material 1212 and moisture and oxygen in a dry environment, lowering the probability of its deterioration, but also reduces the complexity of lithium replenishment processes for the lithium material 1212 in oily or non-polar solvents. Furthermore, the coating layer 1211 in this embodiment can also reduce side reactions between the lithium material 1212 and aqueous solvents, thereby improving the chemical stability of the negative electrode. Therefore, this coating layer 1211 design not only simplifies the negative electrode lithium replenishment process but also further enhances the stability of the negative electrode.

[0062] Meanwhile, the modified polyurethane comprises both flexible and rigid segments, and the synergistic effect of these two segments enhances the mechanical stability and ion transport capability of the coating layer 1211. For example, the flexible segments may include ester groups, while the rigid segments may include aromatic structures. Specifically, in terms of mechanical stability, the flexible segments provide elasticity to the coating layer 1211, while the rigid segments provide mechanical strength. Therefore, the synergistic effect of these two segments results in a moderate balance of softness and hardness in the modified polyurethane. For the lithium material 1212 particles, this facilitates the separation of the coated particles, thereby increasing the stability of the lithium supplement material 121. Furthermore, in terms of ion transport performance, the flexible segments can provide ion transport channels through their own movement after electrolyte injection, thereby improving its ion transport capability.

[0063] In some embodiments, the modified polyurethane includes at least one of a polyurethane-polyimide copolymer, a polyurethane-polycarbonate copolymer, and a polyurethane-polystyrene copolymer. The polyimide, polycarbonate, and polystyrene polymers all have aromatic structures, and copolymerizing these polymers with polyurethane is beneficial for further improving the stability of the coating layer 1211.

[0064] In some embodiments, the molecular weight (MW) of the modified polyurethane satisfies: 100,000 ≤ MW ≤ 1,000,000. For example, MW is 100,000, 200,000, 500,000, 800,000, 1,000,000, or any value within the above range. With a molecular weight within this range, the waterproofing, mechanical strength, and thermal stability of the coating layer 1211 are not weakened due to an excessively low molecular weight, nor are the electrolyte wettability and flexibility affected by an excessively high molecular weight. Therefore, the above molecular weight range is advantageous in balancing the density and mechanical strength of the coating layer 1211 while maintaining its solubility in the electrode solution and ion transport capabilities.

[0065] In some embodiments, the thickness H of the coating layer 1211 satisfies: 10 μm ≤ H ≤ 100 μm. For example, H is 10 μm, 12 μm, 15 μm, 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, or any value within the above range. For the coating layer 1211, if H < 10 μm, the coating effect of the coating layer 1211 on the lithium material 1212 may be affected, thereby reducing the stability of the coating layer 1211. If H > 100 μm, the release rate of the lithium material 1212 from the negative electrode sheet after electrolyte injection may be affected. Simultaneously, an excessively thick coating layer 1211 will also reduce the kinetic performance of the battery and affect its energy density. Therefore, setting the thickness of the coating layer 1211 within the above range is beneficial for enhancing the lithium replenishment effect and improving battery performance.

[0066] In some embodiments, the mass ratio ω1 of the lithium replenishment material 121 to the negative electrode active material layer satisfies: 0.5% ≤ ω1 ≤ 10%. For the negative electrode active material layer, ω1 meeting this range reduces the risk of rapid capacity decay during battery cycling due to insufficient lithium replenishment material 121, thus failing to effectively compensate for lithium ion loss. Conversely, it reduces the risk of excessive lithium replenishment material 121 causing aggravated volume changes in the negative electrode during charging and discharging, thereby damaging the electrode structure. Therefore, setting ω1 within the above range is beneficial for improving the overall performance of the battery.

[0067] In some embodiments, the mass ratio ω2 of lithium material 1212 to the negative electrode active material layer satisfies: 0.1% ≤ ω2 ≤ 5%. Setting the mass ratio of lithium material 1212 to the negative electrode active material layer within the above range helps to reduce the impact of insufficient lithium material 1212 on the lithium replenishment effect. Simultaneously, it also helps to reduce the residual lithium material 1212 due to excessive lithium material 1212. This could potentially cause internal short circuits in the battery or lead to lithium plating on the negative electrode, thereby affecting battery performance. Therefore, this ω2 can improve the overall battery performance while ensuring the lithium replenishment effect.

[0068] It should be noted that the mass ratio of the lithium replenishing material 121 or lithium material 1212 to the negative electrode active material layer refers to the mass ratio of the lithium replenishing material 121 or lithium material 1212 to the solute in the negative electrode active material layer. That is to say, it does not include the mass of the solvent in the negative electrode active material layer, for example, the solvent may include deionized water.

[0069] In some embodiments, the lithium material 1212 includes metallic lithium and lithium-containing compounds. For a single battery cell, a suitable lithium material can be selected based on actual usage requirements. The lithium-containing compounds may include lithium silicon compounds, lithium calcium compounds, lithium magnesium compounds, etc., and this application does not impose any limitations on this.

[0070] In some embodiments, lithium metal includes at least one of lithium powder and lithium foil. Lithium powder has a high specific surface area and high reactivity, enabling rapid compensation for lithium loss, making it suitable for applications requiring efficient lithium replenishment and uniform distribution. However, lithium powder is chemically very reactive and readily reacts with oxygen and moisture, thus requiring operation in an inert environment. In pre-lithiation treatment, lithium powder compensates for lithium loss during the initial charge-discharge cycle through mixing or chemical reactions. On the other hand, lithium foil is relatively stable, with a lower specific surface area and reaction rate, but it is easy to handle and can be operated in air for short periods. Lithium foil, as a lithium replenishment layer, can be directly applied to the surface of the negative electrode, simplifying the process. However, lithium foil has a lower lithium replenishment efficiency and is difficult to distribute uniformly within the negative electrode material.

[0071] For the lithium replenishment material 121, the type of lithium metal can be selected according to the specific application scenario and requirements. For example, lithium powder is suitable for applications requiring high-efficiency lithium replenishment and uniform distribution, while lithium foil is suitable for applications that are easy to operate and do not have high requirements for lithium replenishment efficiency and uniformity. This application does not limit the choice in this regard. It should be noted that, for the sake of convenience, this application uses lithium powder as an example for illustration. For example, Figure 1 The lithium material 1212 in the text is lithium powder.

[0072] In some embodiments, the particle size D of the lithium powder satisfies: 1 μm ≤ D ≤ 100 μm. For lithium powder, when D < 1 μm, due to volume limitations, the weight ratio of lithium material 1212 to the overall lithium replenishment material 121 decreases, resulting in extremely low lithium replenishment efficiency. Simultaneously, excessively small particle size also easily leads to agglomeration, reducing the actual specific surface area, thereby decreasing reactivity and affecting the lithium replenishment effect. On the other hand, when D > 100 μm, the lithium powder has a small specific surface area, resulting in reduced reactivity and potentially uneven lithium replenishment reaction, affecting electrode stability. Furthermore, excessively large particle size also affects electrode processing performance, increasing the strength requirements of the coating layer 1211. Therefore, setting D within the aforementioned range is beneficial for balancing the lithium replenishment efficiency of the lithium powder and the performance of the battery.

[0073] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode active material layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0074] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0075] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0076] In some embodiments, the negative electrode active material layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0077] In some embodiments, the negative electrode active material layer may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0078] In some embodiments, the negative electrode active material layer may also optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0079] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0080] [Positive electrode plate]

[0081] The positive electrode sheet may include a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, wherein the positive active material layer includes a positive active material.

[0082] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive active material layer is disposed on either or both of the two opposite surfaces of the positive current collector.

[0083] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0084] In some embodiments, the positive electrode active material can be a known positive electrode active material for batteries. As an example, the positive electrode active material may include at least one of the following: lithium-containing transition metal oxides, lithium phosphates with an olivine structure, or materials with a spinel structure. However, this application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNiO2). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM622), LiNi 0.8 Co 0.1 Mn 0.1O2 (also known as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05 At least one of O2 and its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.

[0085] In some embodiments, the positive electrode active material layer may optionally include a binder. As an example, the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0086] In some embodiments, the positive electrode active material layer may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0087] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0088] [Electrolytes]

[0089] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.

[0090] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.

[0091] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0092] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0093] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.

[0094] [Isolation membrane]

[0095] In some embodiments, the secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0096] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0097] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0098] In some embodiments, the battery cell may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.

[0099] In some embodiments, the outer packaging of the battery cell can be a rigid shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the battery cell can also be a flexible package, such as a pouch. The material of the flexible package can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0100] This application does not impose any particular limitation on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 2 This is a schematic diagram of a battery cell according to one embodiment of this application.

[0101] Figure 3 This is a schematic diagram of the structure of a battery cell according to another embodiment of this application. Figure 3As shown, the outer packaging of the battery cell 100 includes a housing 11 and a cover plate 13. The housing 11 may include a bottom plate and side plates connected to the bottom plate, the bottom plate and side plates forming a receiving cavity. The housing 11 has an opening communicating with the receiving cavity, and the cover plate 13 can be placed over the opening to close the receiving cavity. A positive electrode sheet, a negative electrode sheet, and a separator can be formed into an electrode assembly 12 through a winding process or a stacking process. The electrode assembly 12 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 12. The battery cell 100 may contain one or more electrode assemblies 12, which can be selected by those skilled in the art according to specific practical needs.

[0102] In some embodiments, the battery cells 100 can also be assembled into a battery module. The number of battery cells 100 contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0103] [Preparation methods for battery cells]

[0104] This application provides a method for preparing a single battery cell, which can improve the first-cycle coulombic efficiency and cycle performance of the battery.

[0105] Figure 4 This is a flowchart illustrating the fabrication process of a battery cell according to one embodiment of this application. Figure 4 As shown, the method 200 for preparing a single battery cell includes the following steps:

[0106] S210 provides a negative electrode sheet, a positive electrode sheet, a separator, and an electrolyte; wherein, the negative electrode sheet includes a negative electrode active material layer, the negative electrode active material layer includes a negative electrode active material and a lithium supplement material 121; the lithium supplement material 121 includes a coating layer 1211 and a lithium material 1212, the coating layer 1211 coating at least a portion of the surface of the lithium material 1212; the coating layer 1211 includes modified polyurethane, the modified polyurethane including an aromatic structure;

[0107] S220 is an electrode assembly obtained by winding or stacking negative electrode sheets, positive electrode sheets, and separators.

[0108] S230 involves immersing the electrode assembly in electrolyte to prepare a single battery cell.

[0109] In the above scheme, the battery cell prepared by this method can enable the battery including the negative electrode to have better first-cycle coulombic efficiency and cycle performance.

[0110] In some embodiments, the modified polyurethane includes at least one selected from polyurethane-polyimide copolymer, polyurethane-polycarbonate copolymer, and polyurethane-polystyrene copolymer. Using these copolymers as modified polyurethanes for the coating layer 1211 is beneficial for improving the stability of the coating layer 1211.

[0111] In some embodiments, polyurethane can be prepared by linear copolymerization with at least one of polyimide, polycarbonate and polystyrene, wherein the copolymerization method includes at least one of block copolymerization, graft copolymerization, crosslinking after blending, living polymerization, step-growth polymerization, solution copolymerization and melt copolymerization. Among these methods, block copolymerization involves reacting an imide polymer containing active end groups with the isocyanate groups of polyurethane to form a block copolymer. These active end groups may include, for example, hydroxyl, amino, or carboxyl groups. Graft copolymerization involves chemically grafting an imide structure onto the main chain or side chains of polyurethane. Post-blending crosslinking involves physically blending an imide polymer with polyurethane and then forming a copolymer network through a crosslinking reaction. Living polymerization methods utilize living polymerization technology to prepare block or graft copolymers containing imide structures; this living polymerization technology may include, for example, atom transfer radical polymerization. Step-growth polymerization directly combines the imide structure with the polyurethane chain through a step-growth polymerization reaction. Solution copolymerization achieves the copolymerization reaction of an imide polymer and polyurethane in a solvent. Melt copolymerization achieves the copolymerization reaction of an imide polymer and polyurethane in a molten state.

[0112] In the preparation of negative electrode sheets, appropriate copolymerization methods can be selected according to actual application requirements. For example, block copolymerization and living polymerization are suitable for the preparation of high-performance, high-precision materials; graft copolymerization is suitable for functional modification; blending followed by crosslinking and melt copolymerization are suitable for large-scale production; solution copolymerization is suitable for the preparation of thin film or coating materials; and stepwise polymerization is suitable for laboratory research and small-scale production.

[0113] Figure 5 This is a flowchart illustrating the preparation process of the negative electrode sheet according to one embodiment of this application.

[0114] In some embodiments, when the lithium material 1212 is lithium powder, the above steps for providing the negative electrode sheet include:

[0115] S211 provides lithium supplementation material 121;

[0116] S212, the negative electrode active material, lithium supplement material 121, conductive agent, binder and thickener are added to deionized water solvent and stirred or ultrasonically treated to obtain negative electrode slurry;

[0117] S213, the negative electrode slurry is coated on at least one side surface of the negative electrode current collector to obtain a negative electrode sheet.

[0118] For individual battery cells, lithium ions can be consumed during battery cycling due to various factors. These include phase transition deactivation after partial insertion / extraction of the cathode material, irreversible formation of the cathode-electrolyte interphase (CEI) film on the cathode surface, and repeated formation and rupture of the SEI film and deactivation of active material sites at the anode interface. These phenomena can reduce the initial coulombic efficiency of the battery and affect subsequent capacity. Therefore, pre-lithiation treatment with an external lithium source can be used to compensate for lithium ion consumption. However, cathode pre-lithiation may affect the cathode material structure and lithium storage capacity. Therefore, pre-lithiation treatment at the anode is a more effective method.

[0119] In step S212 above, the negative electrode slurry is prepared by uniformly mixing the negative electrode active material and the lithium replenishment material 121, which facilitates the tight adhesion between the negative electrode sheet and the separator. Thus, after electrolyte injection, the coating layer 1211 can dissolve in the electrolyte. The lithium material 1212 can serve as a lithium source, causing the exposed lithium material 1212 to undergo a spontaneous reaction due to its low potential characteristics, thereby pre-replenishing the battery with lithium and effectively compensating for the irreversible lithium loss during the first charge and discharge process. This spontaneous reaction may include, for example, a spontaneous lithium intercalation process, which can replenish the consumption from side reactions and the deactivated lithium intercalation points of the positive electrode, thereby effectively improving the first-cycle coulombic efficiency. Simultaneously, the lithium replenishment material 121 does not affect the redox process of the electrode during this process. Therefore, this method not only improves the first-cycle coulombic efficiency of the battery but also enhances the overall performance of the battery.

[0120] In some embodiments, lithium powder is coated using at least one of the following methods: oil phase suspension method, in-situ coating method, and melting method.

[0121] Among these methods, the oil-phase suspension method disperses lithium powder in an oil-phase medium and then adds a coating agent to form a uniform protective layer, which improves the stability of the lithium powder. This method is simple to operate, produces uniform coating, and has good compatibility, making it suitable for high-energy-density batteries. The in-situ coating method directly generates a protective layer on the surface of the lithium powder, achieving uniform coating. In this method, the lithium powder and the coating layer 1211 are tightly bonded, have low reactivity, and are widely applicable, but the process is complex and costly. The melting method melts the coating material and encapsulates the lithium powder through heating. This method is simple to process, produces a uniform and stable coating layer 1211, but high temperatures may affect the performance of the lithium powder, making it suitable for scenarios requiring high thickness and uniformity of the coating layer 1211. In the application of individual battery cells, the appropriate coating method can be selected according to specific needs.

[0122] Figure 6 This is a flowchart illustrating the fabrication process of the negative electrode sheet according to another embodiment of this application. Figure 6As shown, step S211 above may specifically include:

[0123] S2111, lithium powder is added to silicone oil or hydrocarbon solvent and stirred to obtain a lithium solution;

[0124] S2112, A modified polyurethane solution is added to a lithium solution and stirred to obtain a lithium replenishment material solution;

[0125] S2113, the lithium replenishment material solution is cooled, washed and dried to obtain lithium replenishment material 121.

[0126] Specifically, in step S2111, lithium powder needs to be added to silicone oil or a hydrocarbon solvent in an inert environment. For example, this step S2111 can be prepared in an argon atmosphere. By adding it to a silicone oil or hydrocarbon solvent environment and stirring, uniformly dispersed lithium powder can be obtained.

[0127] It should be noted that the hydrocarbon solvents mentioned above are high-temperature resistant hydrocarbon solvents, such as paraffin wax, microcrystalline wax, kerosene and other hydrocarbon solvents, and this application does not impose any restrictions on them.

[0128] In S2112 and S2113, the modified polyurethane is coated onto the surface of the lithium material 1212 using an oil-phase suspension method, which helps to improve the uniformity and stability of the coating layer 1211.

[0129] This application also provides a battery and an electrical device. The battery and electrical device of this application will now be described with appropriate reference to the accompanying drawings.

[0130] [Battery]

[0131] This application provides a battery, including the battery cell described in the above embodiments.

[0132] Figure 7 This is a schematic diagram of a battery according to one embodiment of this application. Figure 8 This is a schematic diagram of the battery structure according to one embodiment of this application. (Refer to...) Figure 7 and Figure 8 The battery 400 may include a battery box and a plurality of battery cells 100 disposed within the battery box. The battery box includes an upper box 401 and a lower box 402, the upper box 401 covering the lower box 402 to form a closed space for accommodating the battery cells 100. The plurality of battery cells 100 may be arranged in any manner within the battery box.

[0133] The technical solution of this application can be applied to various batteries, such as lithium-ion batteries, lithium metal batteries, sodium-ion batteries, potassium-ion batteries, zinc-ion batteries, magnesium batteries, calcium batteries, etc., and this application does not limit them. It should be noted that, for ease of description, this application uses a lithium-ion battery as an example. For other batteries, the negative electrode active material layer includes a negative electrode active material and a supplementary active material. For example, for a sodium-ion battery, the supplementary active material is a sodium-supplementing material; for a potassium-ion battery, the supplementary active material is a potassium-supplementing material; for a zinc-ion battery, the supplementary active material is a zinc-supplementing material, and this application does not limit them.

[0134] [Electrical appliances]

[0135] This application also provides an electrical device that includes the battery described in the foregoing embodiments. The electrical device includes at least one of the battery cell 100 or battery 400 provided in this application. The battery cell 100 or battery 400 can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0136] For example, Figure 9 This is a schematic diagram of the structure of an electrical device according to one embodiment of this application. Figure 9 As shown, the electrical device is vehicle 1, which can be a gasoline-powered vehicle, a natural gas-powered vehicle, or a new energy vehicle. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. A motor 500, a controller 600, and a battery 400 can be installed inside vehicle 1. The controller 600 controls the battery 400 to supply power to the motor 500. For example, the battery 400 can be installed at the bottom, front, or rear of vehicle 1. The battery 400 can be used to power vehicle 1; for example, it can serve as the operating power source for vehicle 1's electrical system, such as meeting the power requirements for starting, navigation, and operation. In another embodiment of this application, the battery 400 can not only serve as the operating power source for vehicle 1 but also as the driving power source, replacing or partially replacing gasoline or natural gas to provide driving power to vehicle 1.

[0137] As the electrical device, either battery cell 100 or battery 400 can be selected according to its usage requirements.

[0138] The electrical device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the battery for this electrical device, a 100-cell battery or a 400-cell battery can be used.

[0139] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use a single battery cell (100) as their power source.

[0140] [Example]

[0141] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0142] [Example 1]

[0143] Preparation of battery cells:

[0144] (1) Preparation of negative electrode sheet:

[0145] (1.1) Preparation of lithium supplementation materials:

[0146] Preparation of modified polyurethane: Isocyanate-terminated polyimide (PI) and hydroxyl-terminated polyurethane (PU) are mixed in a 1:2 ratio and subjected to chain extension reaction in a reactor at 80-100℃ to obtain modified polyurethane.

[0147] Preparation of lithium supplementation material: Under an argon atmosphere, lithium powder was added to silicone oil and stirred. After the lithium powder was fully dispersed, a modified polyurethane solution was added, and stirring continued. Then, the suspension was cooled, washed with n-hexane, and vacuum dried to obtain lithium powder coated with modified polyurethane, i.e., the lithium supplementation material.

[0148] (1.2) Preparation of negative electrode sheet:

[0149] Artificial graphite, lithium-supplementing material, conductive carbon black, styrene-butadiene rubber (SBR) binder, and sodium carboxymethyl cellulose (CMC) thickener were mixed uniformly in a mass ratio of 96.5:0.5:0.4:1.5:1.1. Deionized water was then added as a solvent, and the mixture was stirred until homogeneous, yielding a negative electrode slurry with a solid content of 60 wt%. The negative electrode slurry was then uniformly coated, dried, and cold-pressed to obtain the negative electrode sheet.

[0150] (2) Preparation of the positive electrode sheet:

[0151] Lithium iron phosphate, conductive carbon black, polyvinylidene fluoride, and a dispersant were mixed uniformly in a mass ratio of 97.2:0.7:1.8:0.3. N-methylpyrrolidone solvent was then added, and the mixture was stirred until homogeneous, yielding a positive electrode slurry with a solid content of 63 wt%. The positive electrode slurry was then uniformly coated onto an aluminum foil current collector, dried at high temperature, and finally cold-pressed to obtain the positive electrode sheet.

[0152] (3) Separation membrane: A polyethylene film with a thickness of 13μm is used as the separation membrane.

[0153] (4) Preparation of electrolyte: Ethyl carbonate, diethyl carbonate, and dimethyl carbonate were mixed in a volume ratio of 1:1:1. Lithium hexafluorophosphate was dissolved in the above solution to obtain the electrolyte. The concentration of lithium hexafluorophosphate in the electrolyte was 1 mol / L.

[0154] (5) Preparation of lithium-ion batteries: The above-mentioned positive electrode, separator, and negative electrode are stacked and wound in the order of "separator, negative electrode, separator, positive electrode" to obtain an electrode assembly. The electrode assembly is then placed in a housing, and the electrolyte prepared above is added. After processes such as encapsulation, settling, formation, and aging, a battery cell is obtained. In this case, one end of the positive electrode, negative electrode, and two separators is fixed to the discharge roller, and the other end is stacked together and fixed to the winding shaft. The winding shaft is rotated using a motor to wind the positive electrode, negative electrode, and two separators to obtain a wound battery.

[0155] [Examples 2-3]

[0156] The difference between Examples 2-3 and Example 1 is that the coating layer uses different modified polyurethane materials.

[0157] [Examples 4-5]

[0158] The difference between Examples 4-5 and Example 1 is that the molecular weight of the modified polyurethane is different.

[0159] [Examples 6-7]

[0160] The difference between Examples 6-7 and Example 1 is that the thickness H of the coating layer is different.

[0161] [Examples 8-10]

[0162] The difference between Examples 8-10 and Example 1 is that the mass ratio ω1 of the lithium replenishment material to the negative electrode active material layer is different.

[0163] [Comparative Example 1]

[0164] The difference between Comparative Example 1 and Example 1 is that the negative electrode active material layer does not include lithium supplementation material, and the mass ratio of artificial graphite, conductive carbon black, negative electrode binder styrene-butadiene rubber, and thickener sodium carboxymethyl cellulose is 97:0.4:1.5:1.1.

[0165] [Comparative Example 2]

[0166] The difference between Comparative Example 2 and Example 1 is that the coating material is an unmodified polyurethane material.

[0167] [Comparative Examples 3-6]

[0168] The difference between Comparative Examples 3-6 and Example 1 is that the coating materials are PI, polyacrylic acid (PAA), polydimethylsiloxane (PDMS), and polyethylene oxide (PEO), respectively.

[0169] Table 1 shows the specific parameters of the negative electrode sheet during the preparation of the battery cell, and Tables 2 to 5 show the relevant test results of the battery cell.

[0170] Table 1. Specific parameters of Examples 1-10 and Comparative Examples 1-2

[0171]

[0172]

[0173] In Table 1, "MW" refers to the molecular weight of the modified polyurethane, "H" refers to the thickness of the coating layer, and "ω1" refers to the mass ratio of the lithium supplement material to the negative electrode active material layer.

[0174] [Physical Characterization of Negative Electrode Active Material Layer Materials]

[0175] (1) Surface morphology characterization

[0176] Surface morphology was characterized by scanning electron microscopy (SEM), and the thickness of the coating layer was measured by SEM.

[0177] (2) Molecular weight measurement

[0178] Molecular weight determination was performed using gel permeation chromatography (GPC). The GPC molecular weight determination method involved dissolving the polymer in N-methylpyrrolidone (NMP) at a concentration of 5 mg / mL and allowing it to stand overnight to allow the molecular chains to fully expand. Then, the prepared polymer solution was injected into the GPC column using a syringe. The instrument then automatically performed the test and processed the results.

[0179] (3) Component testing of negative electrode sheet

[0180] For the component detection of the negative electrode sheet, the components can be detected by any means possible in the art. For example, infrared spectroscopy can be used to determine the characteristic peaks contained therein, thereby identifying the types of modified groups. Specifically, infrared spectroscopy analysis of the material can be performed using instruments and methods known in the art, such as an infrared spectrometer (e.g., the Nicolet IS10 Fourier transform infrared spectrometer), according to the General Rules for Infrared Spectroscopic Analysis in GB / T 6040-2019.

[0181] (4) Element content testing

[0182] Discharge the battery cell to 0% SOC at 25℃ and 1 / 3C rate, disassemble the battery cell, and remove the negative electrode plate.

[0183] The negative electrode active material layer of the negative electrode sheet is scraped off and added to aqua regia for digestion under mechanical stirring and high temperature and pressure for 30 minutes. The digested solution is then added to an ICAP7400 spectrometer (EPA 6010D-2018) to analyze the elemental content. For example, the mass content of lithium is calculated as: mass of lithium / mass of all elements in the negative electrode active material layer.

[0184] (5) Measurement of the water-impermeability of the coating layer

[0185] Water resistance was tested using a 20 μm thick coating layer. Specifically, the coated lithium powder and deionized water were mixed at a ratio of 1:1000 at 25°C, and the lithium ion content of the aqueous solution was tested at each time period, recording the time when the lithium ion content was ≤200 ppm.

[0186] (6) Measurement of the solubility of the coating layer in the electrolyte

[0187] Place 1g of polymer block into 20ml of electrolyte, seal, maintain a constant temperature of 60℃, and record the time it takes for the polymer to completely dissolve.

[0188] [Performance Characterization of Lithium-ion Batteries]

[0189] (1) Power performance test

[0190] The power performance of a secondary battery is characterized by its direct current resistance (DCR). Generally, the lower the DCR, the better the battery's power performance.

[0191] The DCR test method can refer to the method in GB / T 31467 "Performance Test Specification for High-Power Lithium-ion Power Batteries for HEVs".

[0192] For example, at 25°C, the lithium-ion battery is charged to 4.25V with a constant current of 0.33C and left to stand for 1 minute; then charged to 4.25V with a constant current of 0.1C and left to stand for 30 minutes; then discharged to 2.8V with a constant current of 0.33C, and the discharge capacity A0 at this point is recorded in Ah. Then, the battery is charged to 0.5A0Ah with a constant current of 0.33C, and the SOC is adjusted to 10%, 20%, 50%, and 90% in sequence.

[0193] After placing the battery at -20℃ for 2 hours, it was discharged at a constant current of 4C for 10 seconds, and ΔU was recorded. 放电 ΔI 放电 Then, the battery was charged with a constant current of 0.01C for 4000s, and the load was adjusted to 10%, 20%, 50%, and 90% SOC. The battery was then left to rest at -20℃ for 2 hours, and then charged with a constant current of 0.1C for 10s. ΔU was recorded. 充电 ΔI 充电 The discharge and charge DCR data of lithium-ion batteries can be calculated using the following formula.

[0194] R 放电 =ΔU 放电 / ΔI 放电

[0195] R 充电 =ΔU 充电 / ΔI 充电

[0196] Wherein, ΔU 放电 ΔI represents the voltage change within 10 seconds of the start of discharge. 放电 ΔU represents the current value within 10 seconds of the start of discharge. 充电 ΔI represents the voltage change within 10 seconds of the start of charging. 充电 This indicates the change in current within 10 seconds of the start of charging.

[0197] (2) Measurement of the first-cycle coulomb efficiency

[0198] The battery was tested using the Blue Electric testing system for charge and discharge.

[0199] Under conditions of 45℃, the battery charge / discharge voltage range was maintained at 2V, and the battery was cycled at a current density of 1C. The charge / discharge capacity of the battery was recorded at the third cycle, and the capacity ratio of discharge to charge was calculated. The test results are shown in Table 3. It should be noted that the first cycle of the battery is the formation stage, and the third cycle is more stable than the second cycle. Therefore, the third cycle was chosen as the first cycle in the practical sense of this application.

[0200] (3) Cyclic performance testing

[0201] The battery was tested using the LAND CT2001A battery tester, employing a constant current charge-discharge method to study its constant current cycle performance. The capacity test process included: first, allowing the battery to rest for 10 minutes; then discharging at 0.2C to a voltage of 2.0V, recording the discharge capacity C0; next, charging at a constant current of 0.5C to 3.65V, followed by constant voltage charging at 0.05C to 3.65V; then discharging at 0.33C to 2.5V, recording the capacity D1, and allowing it to rest for 10 minutes; then discharging at 0.01C to 2.0V, recording the capacity D2; then allowing it to rest for 10 minutes, followed by constant current charging at 0.2C to 3.65V; finally, allowing the battery to rest for 10 minutes.

[0202] 5℃ 1C / 1C Capacity Retention Rate Test: The battery cell was placed in a 25℃ environment and left to stand for 2 hours. After the battery temperature reached 25℃, it was charged at a constant current of 1C and constant voltage to 3.65V, then charged at constant voltage to the cutoff current of 0.05C, left to rest for 5 minutes, and then discharged at 1C to 2.5V. The initial capacity Q0 was recorded, and the capacity after each cycle was recorded. The capacity of the previous discharge cycle was taken as the battery capacity Q2, and the capacity retention rate (%) was calculated. The cycle capacity retention rate = Q2 / Q0 × 100%. The capacity retention rate of the battery cell after 800 cycles was recorded.

[0203] 45℃ 1C / 1C capacity retention rate test: Place the cell in a 45℃ environment and let it stand for 2 hours. After the battery temperature reaches 45℃, conduct the test according to the 25℃ test procedure and calculate the capacity retention rate at this time.

[0204] Table 2. Test results of water resistance and electrolyte solubility of the coating layers in Examples 1-3 and Comparative Examples 2-6.

[0205]

[0206] In this application, the solubility of the coating layer in the electrolyte is used to characterize the solubility of the coating layer in the electrolyte. The higher the solubility in the electrolyte, the better the solubility of the coating layer in the electrolyte.

[0207] As shown in Table 2, and based on Examples 1-3 and Comparative Examples 2-6, the coating layer used in the embodiments of this application has good water-resistant properties and high solubility in the electrolyte.

[0208] Table 3. Elemental content tests of Examples 1, 8-9, and Comparative Example 1.

[0209]

[0210]

[0211] As shown in Table 3, based on Examples 1, 8-9, and Comparative Example 1, the negative electrode active material layer used in this application has a high lithium content. This means that the lithium replenishment material effectively replenishes the lithium in the battery. Within a certain range, the lithium content can be further increased by increasing the mass ratio of the lithium replenishment material to the negative electrode active material layer.

[0212] Table 4 Performance test results of Examples 1-10 and Comparative Examples 1-2

[0213]

[0214] As shown in Table 4, based on Examples 1-10 and Comparative Examples 1-2, it can be seen that using the batteries in the embodiments of this application, the lithium replenishment material has a relatively small impact on the overall charge-discharge internal resistance of the battery, and the difference in charge-discharge internal resistance is smaller compared to Comparative Examples 1-2. In other words, after the lithium source is released, the residual lithium replenishment material will not deteriorate the battery's kinetics.

[0215] Table 5 Performance test results of Examples 1-10 and Comparative Examples 1-2

[0216]

[0217] In Table 5, "first efficiency" refers to the first coulomb efficiency.

[0218] In this application, the capacity retention rate is used to characterize the cycle performance of the battery. The higher the capacity retention rate, the higher the capacity is retained after the battery has cycled to a specific number of times, which means that the battery has better cycle performance.

[0219] Figure 10 This is a SEM image of a lithium replenishment material according to one embodiment of this application. Specifically, it is a SEM image of the lithium replenishment material represented in Example 1. From Figure 10 It can be seen that the modified polyurethane coating on the surface of the lithium powder results in a smooth and dense surface with uniform particle size. The coated lithium replenishment material has a D50 < 50 μm, enabling it to be uniformly dispersed within the negative electrode active material layer of the negative electrode sheet.

[0220] Figure 11 This is the Fourier transform infrared (FTIR) spectrum of the modified polyurethane according to one embodiment of this application. Specifically, it is the FTIR spectrum of the modified polyurethane represented in Example 1. From... Figure 11 It can be determined that 3377.39cm -1 The location represents the R2NH structure in modified polyurethane, 2927.86 cm⁻¹. -1 The peak at 1725.97 cm⁻¹ represents the CH vibration peak on the benzene ring. -1 The structure is C=O, 1520.02cm -1The peak at 1366.87 cm⁻¹ represents the C=C vibration of the benzene ring. -1 The peak at this location is a characteristic peak of CN.

[0221] As shown in Table 5, based on Examples 1-10 and Comparative Example 1, it can be seen that setting a lithium replenishment material in the negative electrode active material layer can improve the first-cycle coulombic efficiency and cycle performance of the battery within a certain range.

[0222] As shown in Table 5, based on Examples 1-10 and Comparative Example 2, it can be seen that by setting a lithium replenishment material in the negative electrode active material layer and using modified polyurethane as a coating layer, the first-cycle coulombic efficiency and cycle performance of the battery can be improved within a certain range.

[0223] As shown in Table 5, and based on Examples 1-3, for modified polyurethane, using polyurethane-polyimide as the coating material results in better first-cycle coulombic efficiency and cycle performance of the battery.

[0224] As shown in Table 5, based on Examples 1 and 4-5, it can be seen that, within a certain range, further controlling the molecular weight of the modified polyurethane is beneficial to further improve the first-cycle coulombic efficiency and cycle performance of the battery.

[0225] As shown in Table 5, and based on Examples 1 and 6-7, within a certain range, further controlling the thickness of the coating layer is beneficial to further improve the first-cycle coulombic efficiency and cycle performance of the battery.

[0226] As shown in Table 5, based on Examples 1 and 8-10, it can be seen that, within a certain range, increasing the mass ratio of lithium replenishment material to the negative electrode active material layer can improve the first-cycle coulombic efficiency and cycle performance of the battery.

[0227] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A battery cell, characterized in that, include: A negative electrode sheet, wherein the negative electrode sheet includes a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode active material and a lithium supplementation material; The lithium replenishment material includes a coating layer and a lithium material, wherein the coating layer covers at least a portion of the surface of the lithium material; The coating layer comprises modified polyurethane, which has an aromatic structure.

2. The battery cell according to claim 1, characterized in that, The modified polyurethane includes at least one of polyurethane-polyimide copolymer, polyurethane-polycarbonate copolymer, and polyurethane-polystyrene copolymer.

3. The battery cell according to claim 1 or 2, characterized in that, The molecular weight (MW) of the modified polyurethane satisfies: 100,000 ≤ MW ≤ 1,000,000.

4. The battery cell according to any one of claims 1 to 3, characterized in that, The thickness H of the coating layer satisfies: 10μm≤H≤100μm.

5. The battery cell according to any one of claims 1 to 4, characterized in that, The mass ratio ω1 of the lithium replenishment material to the negative electrode active material layer satisfies: 0.5% ≤ ω1 ≤ 10%.

6. The battery cell according to any one of claims 1 to 5, characterized in that, The mass ratio ω2 of the lithium material to the negative electrode active material layer satisfies: 0.1% ≤ ω2 ≤ 5%.

7. The battery cell according to any one of claims 1 to 6, characterized in that, The lithium materials include metallic lithium and lithium-containing compounds.

8. The battery cell according to claim 7, characterized in that, The lithium metal includes at least one of lithium powder and lithium foil.

9. The battery cell according to claim 8, characterized in that, The particle size D of the lithium powder satisfies: 1μm≤D≤100μm.

10. A battery, characterized in that, include: The battery cell according to any one of claims 1-9.

11. An electrical appliance, characterized in that, Includes the battery as described in claim 10.